The Effect of Various Combinations of Peripheral Nerve Blocks on Postoperative Pain in Laparoscopic Cholecystectomy: A Comparative Prospective Study - Zoya Haitov Ben Zikri; Maryna Volis; Andrei Mazur; Tatjana Orlova; Hana Alon; Sara Bar Yehuda; Vladislav Gofman (International Journal of Clinical Practice)
Objectives. Most patients who undergo laparoscopic cholecystectomy (LC) experience moderate to severe pain in the first 24 hours after surgery. The transversus abdominal plane (TAP) is currently used for post-LC analgesia. Posterior, subcostal, or rectus sheath TAP blocks are the conventional approaches used. The aim of the current study was to compare the efficacy of combinations of various peripheral blocks on pain intensity and the use of pain killers, shortly after LC. Methods. This was a prospective, double-blind study, in which 200 patients who were about to undergo a LC procedure were recruited and randomized into 4 groups: patients receiving one of the following: TAP block alone, subcostal Tap block alone, subcostal TAP block with a TAP block, or subcostal TAP with a rectus sheath block. The intensity of pain (VAS score) and the use of painkillers were monitored in the recovery unit and in the department for up to 24 hours after surgery. Results. Pain levels decreased with time from 3.6 ± 3.2 at 30 minutes to 0.9 ± 2.0 at 24 hours after the surgery. Nevertheless, no difference between the various block types groups was noted. The percentage of patients who consumed analgesic medications decreased over time, from 83% at 30 to 21% at 24 hours after surgery. The mean/median number of medications consumed by each of the patients was lower among the patients who received a combination of 2 blocks compared to those who received a single one (mean/median of 2.7/3 and 2.8/3 for the TAP or subcostal TAP blocks, respectively; 2.5/2 and 2.3/2 for the subcostal TAP + TAP or subcostal TAP + rectus sheath blocks, respectively). Conclusion. A combination of peripheral nerve blocks reduced the use of analgesic consumption during the 24 hours after LC surgery, compared to standalone blocks.